2021
DOI: 10.1155/2021/8922798
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trends of the Annual Exposure to PM2.5 Particles in European Countries

Abstract: Background. PM2.5 emission is known as a major challenge to environmental health and is the cause of approximately 7 million deaths annually. This study aimed at investigating the main patterns of PM2.5 trend changes among European countries. Methods. The annual exposure to PM2.5 pollutants was retrieved from the World Bank for 41 countries during 2010 to 2017, and a latent growth model was applied to identify the main patterns using Mplus 7.4 software. Results. Monitoring the overall mean annual exposure to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…PM 2.5 emission is known as a major challenge to environmental health and is the cause of approximately 7 million deaths annually (Alikhani et al 2021). Epidemiological research has shown that PM 2.5 will be a serious threat to human health (Ortega-Rosas et al 2021;Thangavel et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 emission is known as a major challenge to environmental health and is the cause of approximately 7 million deaths annually (Alikhani et al 2021). Epidemiological research has shown that PM 2.5 will be a serious threat to human health (Ortega-Rosas et al 2021;Thangavel et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In India, approximately 1 million people died in 2015 due to health problems caused by environmental particulate pollution (Guo et al ., 2017). Data from the World Health Organization (WHO) data have shown a causal link between long‐term exposure to PM 2.5 air pollution and premature deaths, accounting for approximately 7 million deaths globally each year (Alikhani Faradonbeh et al ., 2021). In their October 2013 report, the International Agency for Research on Cancer (IARC) recognized air pollution as ‘carcinogenic to humans’, and inhalable particulate matter (PM 2.5 ) was assigned a ‘class I carcinogen’ status.…”
Section: Introductionmentioning
confidence: 99%